Сучасні методи ідентифікації олій та жирів у технохімконтролі жиропереробного виробництва - Левчук, І. В.; Кіщенко, В. А.; Тимченко, Валентина Кузьмівна; Куниця, Катерина Вікторівна (НТУ "ХПІ", 2015)
У статті представлено результати досліджень жирнокислотного, ацилгліцеринового складу та складу стеринової фракції сумішей рослинних і тваринних жирів. Показано, що сучасні способи ідентифікації олій та жирів повинні застосовувати комплекс аналітичних методів газорідинної хроматографії та хроматомас-спектроскопії. Науково обґрунтовано необхідність перегляду схем технохімічного контролю початкової сировини жиропереробного виробництва.

There is the acute problem of adulteration of food and food raw materials, particularly oil and fat in Ukraine today. The main analytical technique used to identify edible vegetable oils, is the determination of the total fatty acid composition, however, this method is not always possible to determine the composition of mixtures of fats. The article presents the research results of fatty acid and acylglycerols structure and composition of the sterol fraction of model mixtures of milk fat with alien fats of animal and vegetable origin. The developed method is a comprehensive approach to the identification of milk fat, which includes the analysis of fatty acid composition, acylglycerols structure and composition of the sterol fraction. For detection of adulteration of milk fat according to acylglycerols composition defined boundaries define alien fats, which range from 2-10 %. According acylglycerols composition of model mixtures of milk fat palm oil (natural and hydrogination) developed a computational method for determining the content of palm oil fatty basis spreads and other fatty substances, which allows to determine the content of palm oil in the fatty bases spreads and other fatty compounds. Practical recommendations regarding the need to revise the schemes technochemical control in the production of spreads, margarine, blended vegetable oils, confectionery, culinary, bakery and dairy fats by using modern methods of identification of oils and fats using chromatographic methods research.
Modern methods for the identification of oils and fats in tekhnokontrol inoperative production
Keywords: жирнокислотний склад; ацилгліцериновий склад; оліє-жирова сировина; склад стеринів; газорідинна хроматографія; якість продукції; жир молочний; олія пальмова; oil raw materials; fatty raw materials; fatty acid composition; acylglycerols composition; composition of sterols; technochemical control